Applied Quantitative Analysis: An inaugural statement - Dr.Eng. Corinthias P. M. Sianipar (Research Synergy Foundation, 2021)
This article marks the inaugural of Applied Quantitative Analysis (AQA) journal. It is founded on the idea of numbers as the first and foremost mathematical object that act as the harbinger of all meaning. The journal aims to provide a medium for researchers and practitioners to exchange and disseminate their theoretical and practical works that employ quantitative analysis methods to their furthest extent. The journal covers research topics and themes in the three branches of sciences (i.e., formal science, natural science, and social science). In addition to discipline-specific studies, the AQA journal encourages multidisciplinary and interdisciplinary works. Basically, this journal accepts manuscript submissions as Research, Review, Method, Commentary, or Book Review articles. For the submission, each article type has its own general structure and particular requirements. On the other hand, this journal continuously establishes its diverse Editorial Board by inviting experienced scholars in the applied quantitative analysis area from different disciplines and geographical locations. As a focal point of publications among quantitative scholars, the journal invites quantitative scientists and researchers to join as reviewers to ensure the solid quality of published papers.